ANALISISI AMANAT DAN NILAI-NILAI GURINDAM KEDUA BELAS DONGENG BUJANG SRI LADANG - Suhardi Suhardi (Jurnal Bahasa Lingua Scientia, 2017)
The purpose of this study was to describe the values ​​Gurindam Twelfth contained in Bujang Sri Ladang fairy tale. This study uses an objective approach, the approach that focuses only on work study itself (fairy tale Bujang Sri Ladang). The method used is descriptive method, which describe the values ​​Gurindam Twelfth contained in Bujang Sri Ladang fairy tale. Data collected by interview, the interviewing community leaders in the city of Tanjungpinang fairytale owner, to obtain data related to the fairy tale Bujang Sri Ladang. Data analysis technique conducted by: (1) describe the synopsis legend Ship Island, (2) describe the mandate of the fabled Bujang Sri Ladang, (3) describe the values ​​Gurindam Twelfth contained in a fairy tale Bujang Sri Ladang, and (4) interprets the value -value Gurindam Twelfth contained in Bujang Sri Ladang fairy tale. The results obtained: Bujang Sri Ladang fairytale field contains: Islamic values, the value of faith, social values, manners and character, introspective, benefits, and ethical values. It is as the result of analyzes performed. Those values ​​are the essential values ​​and become a lifeline of society, especially the Malay community Tanjungpinang city